2021
DOI: 10.1128/jb.00553-20
|View full text |Cite
|
Sign up to set email alerts
|

EslB Is Required for Cell Wall Biosynthesis and Modification in Listeria monocytogenes

Abstract: Lysozyme is an important component of the innate immune system. It functions by hydrolysing the peptidoglycan (PG) layer of bacteria. The human pathogen Listeria monocytogenes is intrinsically lysozyme resistant. The peptidoglycan N-deacetylase PgdA and O-acetyltransferase OatA are two known factors contributing to its lysozyme resistance. Furthermore, it was shown that the absence of components of an ABC transporter, here referred to as EslABC, leads to reduced lysozyme resistance. How its activity is linked … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 50 publications
(108 reference statements)
0
22
0
Order By: Relevance
“…EslA and EslB are predicted to form an ABC transporter; however, it is still unknown whether the transmembrane protein EslC is also part of the ABC transporter or whether it has an independent role of EslAB. Bacterial two-hybrid experiments indicated that EslB and EslC interact with each other [ 80 ], and we will thus refer to the transporter as the EslABC transporter. Phenotypic analysis of strains lacking either EslA or EslB revealed a strong increase in lysozyme sensitivity, and deletion of eslC does not affect lysozyme resistance of L. monocytogenes [ 80 , 81 , 82 ].…”
Section: Abc Transporters Affecting Cell Wall Biosynthesis and Remmentioning
confidence: 99%
See 4 more Smart Citations
“…EslA and EslB are predicted to form an ABC transporter; however, it is still unknown whether the transmembrane protein EslC is also part of the ABC transporter or whether it has an independent role of EslAB. Bacterial two-hybrid experiments indicated that EslB and EslC interact with each other [ 80 ], and we will thus refer to the transporter as the EslABC transporter. Phenotypic analysis of strains lacking either EslA or EslB revealed a strong increase in lysozyme sensitivity, and deletion of eslC does not affect lysozyme resistance of L. monocytogenes [ 80 , 81 , 82 ].…”
Section: Abc Transporters Affecting Cell Wall Biosynthesis and Remmentioning
confidence: 99%
“…Bacterial two-hybrid experiments indicated that EslB and EslC interact with each other [ 80 ], and we will thus refer to the transporter as the EslABC transporter. Phenotypic analysis of strains lacking either EslA or EslB revealed a strong increase in lysozyme sensitivity, and deletion of eslC does not affect lysozyme resistance of L. monocytogenes [ 80 , 81 , 82 ]. This observation does not rule out that EslC might be part of the ABC transporter; however, it suggests that EslA and EslB have an independent role of EslC.…”
Section: Abc Transporters Affecting Cell Wall Biosynthesis and Remmentioning
confidence: 99%
See 3 more Smart Citations